UPAYA INDONESIA MENINGKATKAN EKSPOR KOPI KE MALAYSIA 2018-2021 - Pramudita, Lintang; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the efforts undertaken by Indonesia to increase coffee exports to Malaysia during the period from 2018 to 2021. Malaysia is one of the main export destinations for Indonesian coffee in the Southeast Asian region, with a growing trend in coffee consumption, particularly among the younger generation and players in the beverage industry. In this context, Indonesia faces challenges such as competition from other coffee-producing countries like Vietnam and Brazil, as well as increasing demands regarding quality, certification, and complex market preferences. This research employs a descriptive qualitative approach using international political economy theory from a liberalism perspective and the theory of comparative advantage as analytical frameworks. Data were collected through literature review and documentation from secondary sources such as official reports, statistical data, and academic literature. The results of the study show that the Indonesian government's strategy to boost coffee exports to Malaysia includes improving product quality, promoting through international exhibitions and coffee festivals, leveraging the ASEAN free trade agreement (ATIGA), strengthening economic diplomacy, and digitalizing marketing efforts. In addition, support for farmers and MSMEs through training, quality standardization, and the strengthening of infrastructure and logistics also plays a role in maintaining the competitiveness of national coffee exports. Keywords: International Trade, Comparative Advantage, Economic Diplomacy.